PERANCANGAN DAN PENGEMBANGAN SISTEM INFORMASI PERPUSTAKAAN ONLINE PADA SMK NEGERI 1 BOJONGGEDE BOGOR - Dwi Yusrini; Yoseph Tajul Arifin; Norma Yunita (Paradigma, 2018)
The existence of a library in a school becomes very important as a supporter of student learning activities. SMK Negeri 1 Bojonggede with the quite a lot  of learners, has facilitated the students by creating their own library and book collection enough to meet the needs of students and teachers. The large number of books and the intensity of borrowing students on library books becomes a challenge for the library. Based on interviews with the head of the library said that there are various obstacles in library services, such as technical management of book collection data, technical management of borrowing and return of books and follow up cases of damages and loss of collection of books in libraries or borrowed by members of the library. In this study the authors analyze various proposals for problem solving as well as improve the system at the library as well as developing an online library system for service activities and library management in SMK Negeri 1 Bojonggede.